Predictive value of the combination of brachial-ankle pulse wave velocity and ankle-brachial index for cardiovascular outcomes in patients with acute myocardial infarction. Issue 2 (March 2020) - Park, Hyun-Woong; Kim, Hye-Ree; Kang, Min Gyu; Kim, Kyehwan; Koh, Jin-Sin; Park, Jeong Rang; Hwang, Seok-Jae; Jeong, Young-Hoon; Ahn, Jong Hwa; Park, Yongwhi; Hwang, Jin-Yong
Abstract : Background: Although ankle-brachial index and brachial-ankle pulse wave velocity measurement are well-established modalities for assessing peripheral artery disease and arterial stiffness and predicting cardiovascular events, it is unclear which one is more important or if a combination of the two is more effective for determining prognosis among patients with acute myocardial infarction. Methods: Patients with acute myocardial infarction (n = 889) were stratified into four groups according to a brachial-ankle pulse wave velocity (cut-off value: 1684 cm/s) and ankle-brachial index (cut-off value: 0.98): group I (high ankle-brachial index and low brachial-ankle pulse wave velocity, n = 389), group II (high ankle-brachial index and high brachial-ankle pulse wave velocity, n = 281), group III (low ankle-brachial index and low brachial-ankle pulse wave velocity, n = 103), group IV (low ankle-brachial index and high brachial-ankle pulse wave velocity, n = 116). The mean follow-up duration was 348 days. Results: Major adverse cardiovascular events or cardiac death occurred in 64 (7.2%) and 26 patients (2.9%), respectively. In multivariable analysis, group III and IV had a significant high hazard ratio for major adverse cardiovascular events (5.93, 5.43) and cardiac death (13.51, 19.06). Additionally, ankle-brachial index had a higher hazard ratio than brachial-ankle pulse wave velocity for major adverse cardiovascular events (3.38 vs. 1.40) and cardiac death (6.21 vs. 2.40). When comparing receiver operating characteristic curves of the combined models of risk factors, brachial-ankle pulse wave velocity, and ankle-brachial index, pulse wave velocity plus ankle-brachial index or pulse wave velocity plus ankle-brachial index plus risk factors were significantly more predictive of major adverse cardiovascular events than risk factors. Conclusion: Our findings indicate that ankle-brachial index is a strong independent prognostic factor and adding a brachial-ankle pulse wave velocity measurement to ankle-brachial index increases the prognostic power for cardiac events in patients with acute myocardial infarction, while ankle-brachial index and pulse wave velocity showed additive value to risk factors.